Ultrasonographic characterization of alveolar liquids in Brazilian Portuguese speaking children: target and substituted productions - Esperandino, Cássio Eduardo [UNESP]; Berti, Larissa Cristina [UNESP] (FapUNIFESP (SciELO), 2023)
Although liquid consonants have been described as complex segments because they involve the simultaneous production of double articulatory gestures, tip and dorse, and are commonly involved in phonological simplification processes, there are contrary arguments in this regard, and there is no consensus in the literature. Therefore, this study aimed to describe the correct productions of alveolar liquids and the simplification processes (semivocalization and substitution) of /ɾ/ of Brazilian Portuguese in 30 children aged 4 to 9 years from an ultrasound analysis of the tongue. The correct productions were described as having double gestures (tip and dorse) for both phonemes, with higher tip and more anterior dorse for [ɾ] compared to [l]. In productions with substitution (/ɾ/à [l]), there was a pattern very close to correct productions of /ɾ/, however, with subtle differences in magnitude in tip elevation. For the substitution of /ɾ/à [j], only an elevation of the medial portion of the tongue (body of the tongue) was observed, with no elevation of the tip (gestural fusion). Brazilian Portuguese alveolar liquid consonants are complex segments. The posterior tongue gesture has always been present.
Caracterização ultrassonográfica das líquidas alveolares de crianças falantes do Português Brasileiro: produções alvo e substituídas
Keywords: child; phonetics; speech sound disorders; ultrasound